Analisis Filsafat Pendidikan Terhadap Pembentukan Karakter Siswa Di Sekolah Dasar - Panggabean, Dwi Utami; Matondang, Tuti Alawiyah; Nasution, Dedek Oktavia; Tarihoran, Faizah Rahmi; Siregar, Pahri (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2026)
Character building in elementary school students is a crucial issue in education, particularly amid the challenges of moral crises and social changes in the technological era. Educational philosophy is viewed as a fundamental foundation for designing values, goals, and educational practices oriented toward character development. This study aims to analyze the role of educational philosophy in shaping the character of elementary school students through a Systematic Literature Review (SLR) approach. This study employs the SLR method, following the PRISMA 2020 guidelines, through a systematic process of identification, selection, and synthesis of the literature. The literature search was conducted using databases such as Google Scholar, SINTA, and reputable international journals within the publication range of 2020–2025. Of the 72 identified articles, 18 met the inclusion criteria and were further analyzed using thematic analysis. The results indicate that educational philosophy, particularly the streams of idealism, pragmatism, and progressivism, plays a significant role in shaping students’ character values such as honesty, responsibility, discipline, cooperation, and empathy. The integration of these three philosophical approaches has been proven to produce more holistic, contextual, and applicable learning processes in students’ daily lives. Furthermore, the implementation of philosophical values in learning enhances students’ moral awareness and positive behavior. Therefore, educational philosophy has a strategic role as a conceptual foundation in character building for elementary school students. This study emphasizes the importance of integrating philosophical values into the curriculum, learning strategies, and the role of teachers as role models in instilling character values sustainably.